Insular dysfunction of interoception in major depressive disorder: from the perspective of neuroimaging - Hu, Lan; He, Hui; Roberts, Neil; Chen, Jiajia; Yan, Guojian; Pu, Li; Song, Xufeng; Luo, Cheng (Frontiers in Psychiatry, 2023)
Interoception plays a crucial role in maintaining bodily homeostasis and promoting survival, and is considered the basis of human emotion, cognition, and self-formation. A malfunction of interoception is increasingly suggested to be a fundamental component of different mental health conditions, and depressive disorders have been especially closely associated.Interoceptive signaling and processing depends on a system called the "interoceptive pathway", with the insula, located in the deep part of the lateral fissure, being the most important brain structure in this pathway. Neuroimaging studies have revealed alterations in the structure and function of the insula in a large number of individuals with depression, yet the precise relationship between these alterations and interoceptive dysfunction remains unclear. The goal of this review is to examine the evidence that exists for dysfunction of interoception in people with Major Depressive Disorder (MDD), and to determine the associated specific alterations in the structure and function of the insula revealed by neuroimaging. Overall, three aspects of the potential relationship between interoceptive dysfunction and alterations in insular function in people with depression have been assessed, namely clinical symptoms, quantitative measures of interoceptive function and ability, and interoceptive modulation. To conclude, several specific limitations of the published studies and important lines of enquiry for future research are offered.